Phylogenetic position of the endemic Mount Oku rat, Lamottemys okuensis (Rodentia: Muridae), based on molecular and morphological data. (18th December 2015) - Missoup, Alain Didier; Nicolas, Violaine; Eiseb, Seth; Chung, Ernest Keming; Denys, Christiane
Abstract : L amottemys okuensis Petter, 1986, is restricted to the Mount Oku montane forest in the central‐northern part of the Cameroon Volcanic Line (CVL; Central West Africa). It is endangered and has a decreasing population trend. The genus is monotypic and little is known about its phylogeny and evolutionary history. Using both molecular and morphological evidence, we tested two competing systematic hypotheses involving L amottemys : whether it is more closely related to D esmomys or to O enomys . We also discuss L amottemys ' biogeographical origin. Molecular phylogenies indicated a sister‐group relationship with the Ethiopian montane forest endemic genus D esmomys . This reinforces the hypothesis of recurrent connections over time between West and East African mountains, probably facilitated by climate changes that led to expansions and contractions of montane environments. Our molecular dating, consistent with a period of intense volcanic activity in Central East Africa and the CVL, suggests that the geological history of East and Central Africa also contributed to promoting the isolation of L amottemys in the CVL. Moreover, this study provides the most comprehensive phylogenetic analysis for the whole tribe Arvicanthini, sampling 17 of the 18 member genera. In this rodent group, stephanodonty probably appeared independently with grasses expansion. These habitat changes probably promoted the evolution of specialist rodents able to feed on abrasive vegetal matter by a dental adaptation.